AN IN-DEPTH ANALYSIS OF THE CONCEPT OF A DESIGNER IN THE ERA OF FASHION DEVELOPMENT - Islamova Rahbarkhan Ravshanovna; Elibayeva Mukhlisa Sharofovna (Bright Mind Publishing, 2025)
Fashion is not just a means of dressing your body, it is the essence of your personality and beliefs. Designers are well aware of the pioner they have. Fashion can change from one second to the next, but what never changes is the impact it has on society and the role it plays in the modern world. Fashion is so important that entire magazines are devoted to it, TV programs devote hours to the topic, and people constantly discuss it among their friends.
Keywords: Fashion, design, technology, trend, fabric, national, art, designer, influence of fashion, revolution.